2007
DOI: 10.1021/ol7025087
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Isomer of Nonaromatic Porphyrin:  Preparation of 20π-Conjugated Porphycene Based on Electronic Perturbation

Abstract: A porphycene having four CF3 groups at the beta-pyrrolic positions affords a stable 20pi-conjugated form in the presence of a 2H+-2e- donor due to the high redox potential of the tetrapyrrole ring framework. No visible band in the UV-vis spectrum and the highly ruffled structure determined by X-ray crystallography support its nonaromatic character. The ethylene bridge moiety in the 20pi-conjugated framework displayed the olefinic reactivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 10 publications
3
39
0
Order By: Relevance
“…[25] Whereas the optimized molecular structure of [18]EtioPc reveals a quite planar geometry, [18]CF 3 Pc shows a slightly ruffled structure due to the steric/electronic repulsion between bulky trifluoromethyl substituents (Figure 1). Furthermore, [20] [20] Although the MOs of [18]CF 3 Pc also show a quite similar behavior to [18]EtioPc, the energy stabilization of LUMO was observed due to the existence of electron-withdrawing substituents (Figure 2). This feature is in good accordance with the previously reported electrochemical observation of [18]CF 3 Pc.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[25] Whereas the optimized molecular structure of [18]EtioPc reveals a quite planar geometry, [18]CF 3 Pc shows a slightly ruffled structure due to the steric/electronic repulsion between bulky trifluoromethyl substituents (Figure 1). Furthermore, [20] [20] Although the MOs of [18]CF 3 Pc also show a quite similar behavior to [18]EtioPc, the energy stabilization of LUMO was observed due to the existence of electron-withdrawing substituents (Figure 2). This feature is in good accordance with the previously reported electrochemical observation of [18]CF 3 Pc.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [16] reported in 2007 that trifluoromethyl groups on pyrrole rings give rise to relatively air-stable [20]p porphyrin. After this work, Hayashi et al [17] also reported the successful synthesis and isolation of air-stable [20]p b-tetrakis(trifluoromethyl) porphycene ( [20]CF 3 Pc) through two-electron reduction and two protonation processes of [18]p b-tetrakis (trifluoromethyl)porphycene ([18]CF 3 Pc), which seems to be an analogue of etioporphycene ( [18]EtioPc) (Scheme 1). [18,19] Porphycene, the first porphyrin isomer, was synthesized by Vogel and co-workers in 1986, and a considerable number of research efforts have been conducted on novel synthesis, characterization, and applications of various porphycene derivatives over the past few decades.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations